Propolis as a Treatment Option for Hand, Foot, and Mouth Disease (HFMD) in Children: A Prospective Randomized Clinical Study - Manolya Kara; Murat Sütçü; Ömer Kılıç; Doruk Gül; Tugçe Tural Kara; Gulşen Akkoç; Ayşe Baktır; Şefika Elmas Bozdemir; Özlem Özgür Gündeşlioğlu; Funda Yıldız; Ciğdem Yanar Ayanoğlu; Meltem Bozacı Kılıçoğlu; et al. (Children)
Background: Hand, foot, and mouth disease (HFMD) is a frequently self-limited viral infectious disease that affects children and has no specific antiviral treatment option. There has been increasing interest in bee products in recent years, and propolis has come to the fore due to its impressive therapeutic and protective effects. Although previous studies have shown the inhibitory effect of propolis against enteroviruses (EVs), there are no clinical data regarding its use in combatting HFMD. This prospective multicenter randomized clinical study aimed to evaluate the effect of administering propolis to children with HFMD. Methods: This study analyzed 183 children with HFMD. All children were assessed for eligibility and diagnosed with HFMD by a child health and disease specialist after presenting with symptoms of either fever, enanthem, or exanthems that had begun within the last 48 h. The patients were randomly assigned to the group receiving Anatolian propolis (n = 87) or that receiving no supplement—the control group (n = 96)—in addition to receiving symptomatic therapy as decided by the physician. The duration of the patient’s complaints, the distribution of the lesions on their body, and their fever status were recorded on admission. Parents were asked to rate the severity of their child’s restlessness, inappetence, and sleeplessness on a scale of 0–10 at their initial, second (at 48th hour), and third (after 5–7 days) visits to the hospital. The primary data analysis methods included the Kolmogorov–Smirnov test for normality and non-parametric tests such as the Kruskal–Wallis and Mann–Whitney U tests, which were used for group comparisons. Results: The median age of the patients was 28 months (range: 12–112), and the male-to-female ratio was 1:1. Most patients (62.8%) had no history of a household contact with HFMD. Intraoral lesions were present in 92.3% of patients, and 47.5% received the propolis treatment while 53.5% were in the control group. There was a significant difference between the groups in terms of their complaint scores during their second (p = 0.028) and third (p < 0.001) visits to the hospital. In addition, the mean duration of the illness in the propolis group (7.45 days) was significantly lower than that in the control group (8.58 days) (p < 0.001). No adverse effects were observed. Conclusions: Propolis has been shown to facilitate symptomatic relief and reduce the duration of the disease in children with HFMD. To better assess the efficacy of this product, which can be used safely in children, future studies supported by virological analyses are required.